Social security, benefit claiming, and labor force participation: A quantitative general equilibrium approach - Selahattin çImrohoroæglu; Sagiri Kitao (Federal Reserve Bank of New York, 2010)
We build a general equilibrium model of overlapping generations that incorporates endogenous saving, labor force participation, work hours, and Social Security benefit claims. Using this model, we study the impact of three Social Security reforms: 1) a reduction in benefits and payroll taxes; 2) an increase in the earliest retirement age, to sixty-four from sixty-two; and 3) an increase in the normal retirement age, to sixty-eight from sixty-six. We find that a 50 percent cut in the scope of the current system significantly raises asset holdings and the labor input, primarily through higher participation of older workers, and reduces the shortfall of the Social Security budget through a reduction in early claiming. Increasing the normal retirement age also raises saving and the labor supply, but the effects are smaller. Postponing the earliest retirement age has only a negligible effect. When the projected aging of the population is taken into account, the case for a reform that encourages labor force participation of the elderly appears to be much stronger.
Keywords: E62; H24; H31; 330; Social Security reform; labor force participation; benefit claiming; retirement age; overlapping generations